Changes in customer preferences for furniture in Slovenia : Promjene sklonosti kupaca namještaja u Sloveniji - Jošt, Matej (Array, 2020)
In the last decade, the Slovenian furniture industry market has experienced a number of changes, especially with the arrival of new retailers on the market. The situation is such that furniture manufacturers and retailers are still trying to determine the best ways to adjust to new customer demands. A well known thing is that customer satisfaction is the key component for the success of the business. In order for companies to be more successful, it is important to get better insight into customers’ needs and wants. In line with this, the purpose of this study, which compare the surveys conducted in 2010 and 2019, was to observe and analyse changes in the preferences of customers for furniture: materials, attributes, and styles when deciding on new furniture in Slovenia. The results of this research showed that customers’ preferences for furniture materials have changed in the last decade. Similarly, the factors that influence their purchase decisions when buying interior and exterior furniture have changed as well. It was found that wood was widely preferred as a furniture material among the respondents in both years studied.